2018
DOI: 10.1101/505313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prior Perceptual-Cognitive Training Builds Mental Resistance During Acute Physical Fatigue In Professional Rugby Athletes

Abstract: Elite athletes are engaged in intensive physical training programs because it improves their physical strength and agility, but also to build endurance for resisting the negative impact of fatigue. Although it is well accepted that physical fitness can reduce the consequence of mental fatigue it is still unknown whether specific mental training can reduce the negative impact of physical fatigue on perceptual-cognitive functions. Here we show in professional rugby players that acute physical fatigue can dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…This procedure may have stabilized 3D-MOT performance and eliminated the task-learning effect. However, a preliminary study has shown that prior training of athletes can reduce susceptibility to acute physical fatigue as demonstrated by unaffected 3D-MOT scores, while athletes untrained (not consolidated) on 3D-MOT did show a detrimental effect of acute physical fatigue on 3D-MOT scores (Faubert & Berthes, 2018). Perhaps the same phenomenon is observed here for mental fatigue, given that all the athletes were pre-trained (consolidated) (Faubert & Berthes, 2018).…”
Section: Limitations and Directions For Further Researchsupporting
confidence: 65%
“…This procedure may have stabilized 3D-MOT performance and eliminated the task-learning effect. However, a preliminary study has shown that prior training of athletes can reduce susceptibility to acute physical fatigue as demonstrated by unaffected 3D-MOT scores, while athletes untrained (not consolidated) on 3D-MOT did show a detrimental effect of acute physical fatigue on 3D-MOT scores (Faubert & Berthes, 2018). Perhaps the same phenomenon is observed here for mental fatigue, given that all the athletes were pre-trained (consolidated) (Faubert & Berthes, 2018).…”
Section: Limitations and Directions For Further Researchsupporting
confidence: 65%